Renewing polyethylene: insertion copolymerization of sugar derived hydrophilic monomers with ethylene - Rajput, Bhausaheb S.; Pawal, Sandip B.; Bodkhe, V. Dnyaneshwar; Rao, I. Nagamalleswara; Sainath, Annadanam V. Sesha; Chikkali, Samir H. (European Polymer Journal, 2020)
Although highly desirable, insertion copolymerization of renewable resource derived functional olefins with ethylene has been rarely investigated. Herein, we report insertion copolymerization of challenging sugar derived isohexide mono-enes with ethylene in the presence of Pd-phosphinesulfonate acetonitrile catalyst (C1). Thus, copolymerization of ethylene with isomannide mono-ene (2a), isosorbide mono-ene (2b'), isoidide mono-ene (2c) and methacryl-2,3,4,6-tetra-O-acetyl-D glucopyranoside (2d) afforded corresponding functionalized polyethylene (P2a-1 to P2d-1). High temperature proton NMR investigations revealed enchainment of 2a-2c in polyethylene backbone and the highest incorporation of 1.45% was observed for 2c. The high temperature proton NMR results were further corroborated by solid state C-13 NMR and IR spectroscopy. Gel permeation chromatography analysis displayed weight average molecular weight in the range of 13.0-27.2 x 10(3) g/mol. The thus prepared copolymers revealed melting temperature in the range of 117-126 degrees C. Relatively reduced melting temperature compared to neat polyethylene may suggest an irregular arrangement of pendant functional group on polyethylene main chain.
Keywords: Hydrophilic polyethylene; insertion copolymerization; Isohexide mono-enes; Polyethylene; Sugar

Insertion copolymerization of functional olefins: Quo Vadis? - Birajdar, Rajkumar S.; Chikkali, Samir H. (European Polymer Journal, 2021)
Functional polyethylene is a specialty polymer with unique set of properties and caters to a niche market. Currently, it is manufactured using high-pressure, high-temperature radical polymerization, or post-reactor (indirect) modification methods. Insertion copolymerization of functional olefins with ethylene provides a low pressure, direct route to prepare functional polyethylenes. However, insertion copolymerization of functional olefins with ethylene poses several impediments and requires special considerations. This review presents the current strategies, examines the progress, and attempts to gauge the commercial potential of direct synthesis of functional polyethylene. The performance of late transition metal catalysts derived from a-diimine, imine-phenolate, phosphine-sulfonate, bis-phosphine-mono-oxide, carbene-phenolate, phosphine-phenolate and their derivatives in the insertion copolymerization of functional olefins with ethylene is evaluated. While catalyst designing is crucial, incorporation of polar olefins that can serve an additional purpose is equally important. Therefore, we have organized the review in the following sections, polar alkenes with- acrylates, acrylic acids, acetates, nitriles, ethers, halides, two functional groups, cross-linking groups, dynamic interactions/self-healing properties, additional function/purpose, renewable functional olefins, and examine the progress. Among these, acrylates have been most intensively investigated and have been successfully incorporated in the polyethylene main-chain. Ethylene, methyl acrylate copolymers prepared by direct copolymerization reveal comparable melting temperature to that of LLDPE (at similar co-monomer content) and unfold the commercial potential of these materials. Recent developments on the insertion copolymerization of renewable functional olefins and di-functional olefins have elicited significant interest. This strategy is being viewed as a means of reducing environmental impact and enabling high functional group density at the same extent of incorporation. The overview thus offers a succinct account of insertion copolymerization of functional olefins, sheds light on the copolymer microstructure/material properties, and initiates a discussion on the commercial potential of functional polyethylene.
Keywords: Catalyst; Functional polyethylene; functional polyolefins; Hydrophilic polyethylene; insertion copolymerization; Polyethylene